Parenthesis in Biblical Hebrew - Zewi, Tamar. (Studies in Semitic Languages and Linguistics, 2007)
Parenthesis in Biblical Hebrew has never been examined as an autonomous independent topic. Scholarly references to parenthetical units or parenthetical techniques in Biblical Hebrew are usually scarce and short or entirely absent. This monograph fills this gap by offering a comprehensive description of parenthetical clauses and parenthetical words and phrases in Biblical Hebrew, through integration of several research disciplines and scholarly approaches: linguistics, discourse studies, text linguistics, textual philology, comparative Semitics, Bible translations, and literature. Special attention is paid to the analysis of the linguistic aspects of parenthesis, the identification and definition of which are particularly elusive.